New distributional records for the asopine pentatomids in temperate South America - Dellapé, Pablo Matías; Martínez, Auria Paula; Coscarón, María Del Carmen (Zootaxa, 2003)
New records of species of the subfamily Asopinae (Pentatomidae) of Argentina and adjacent countries are presented. A total of 34 species and 17 genera has been recorded for this region. The material studied belongs to the Museo Argentino de Ciencias Naturales, Buenos Aires, and to the Museo de La Plata, Argentina. Oplomus salamandra, Stiretrus loratus, and Tylospilus distans are new records for Argentina; Tylospilus chilensis for Bolivia; Tylospilus distans for Chile; Alcaeorrhynchus grandis and Oplomus cruentus are cited for the first time for Paraguay; and Discocera cayennensis, Podisus nigrispinus, and Podisus australis for Uruguay. The geographic distributions of the species are mapped.